Analisis Penerapan Metode Field Trip dalam Pembelajaran Teks Deskripsi Kelas VII SMP Negeri 3 Gemuh: Analysis of the Application of the Field Trip Method in Descriptive Text Learning for Class VII of SMP Negeri 3 Gemuh - Eva Nadia Ariani; Ngatmini Ngatmini; Agus Wismanto (ITScience (Information Technology and Science), 2026)
This research is motivated by students' low ability to transform visual objects into specific written diction in descriptive text learning. So far, learning has tended to be abstract and centered on textbooks, making it difficult for students to describe objects in detail, concretely, and meaningfully. This study aims to analyze the application of the field trip method in descriptive text learning for seventh-grade students of SMP Negeri 3 Gemuh. The study used a descriptive qualitative method. Data were collected through participatory observation, in-depth interviews with Indonesian language teachers and students, and analysis of student work. The results showed that the field trip method significantly increased students' sensory involvement, as students wrote based on direct observation rather than abstract imagination. This condition affects the quality of descriptive text, particularly the richness of diction, the accuracy of details, and students' ability to use the five senses in writing. Students also appeared more active and enthusiastic, and found ideas more easily during the learning process. From the teacher's perspective, this method helps students compose descriptions more coherently and contextually. However, its implementation still faces obstacles in time management and classroom control. These obstacles can be minimized by using structured Student Worksheets (LKS) as observation guides. Thus, the field trip method has proven effective in improving the quality of learning in descriptive text.